Discontinuation of dasatinib in patients with chronic myeloid leukaemia who have maintained deep molecular response for longer than 1 year (DADI trial): a multicentre phase 2 trial. Issue 12 (December 2015) - Imagawa, Jun; Tanaka, Hideo; Okada, Masaya; Nakamae, Hirohisa; Hino, Masayuki; Murai, Kazunori; Ishida, Yoji; Kumagai, Takashi; Sato, Seiichi; Ohashi, Kazuteru; Sakamaki, Hisashi; Wakita, Hisashi; et al.
Summary: Background: First-line imatinib treatment can be successfully discontinued in patients with chronic myeloid leukaemia after deep molecular response has been sustained for at least 2 years. We investigated the safety and efficacy of discontinuing second-line or subsequent dasatinib after at least 1 year of deep molecular response. Methods: The Dasatinib Discontinuation trial was a prospective multicentre trial done in Japan. Eligible patients taking dasatinib and with confirmed stable deep molecular response were enrolled between April 1, 2011, and March 31, 2012. All patients received dasatinib consolidation therapy for at least 1 year. In those with sustained deep molecular response, dasatinib was discontinued. Patients were followed up every month in year 1 (clinical cutoff), every 3 months in year 2, and every 6 months in year 3 for deep molecular response and immunological profiles. The primary endpoint was the proportion of patients with treatment-free remission at 6 months after discontinuation. Molecular relapse was defined as loss of deep molecular response at any assessment. This study is registered, number UMIN000005130. Findings: 88 patients were enrolled in the consolidation phase, 24 were excluded from the discontinuation phase due to fluctuations in BCR-ABL1 transcript levels. One patient was excluded because of positive expression of major and minor BCR-ABL1 transcripts in chronic myeloid leukaemia cells and the detection of minor BCR-ABL1 transcripts during consolidation. Thus, 63 patients discontinued dasatinib treatment. The 25 patients who were excluded from discontinuation continued to receive dasatinib and none showed disease progression. Median follow-up was 20·0 months (IQR 16·5–24·0). Of the 63 patients who discontinued and were not excluded, 30 patients maintained deep molecular response while 33 patients had molecular relapses, all within the first 7 months after discontinuation. The estimated overall treatment-free remission was 49% (95% CI 36–61) at 6 months. No severe treatment-related toxic effects were seen. Treatment was restarted in the 33 patients with relapse; rapid molecular responses were seen in all 33 patients, of whom 29 (88%) regained deep molecular response within 3 months, as did the remaining four by 6 months. Interpretation: Dasatinib discontinuation after sustained deep molecular response for more than 1 year is feasible. Funding: Epidemiological and Clinical Research Information Network (ECRIN).